Gerakan Bersih Sungai oleh Mahasiswa sebagai Upaya Menciptakan Lingkungan yang Asri dan Berkelanjutan - Rahayu Mardikaningsih; Widelia Putri Nabila; Mila Hariani; Fayola Issalillah; Masfufah Masfufah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
River clean-up activities represent a collaborative effort involving students and the community aimed at reducing environmental pollution, improving river ecosystem quality, and fostering sustainable ecological awareness. This program was implemented using the Asset-Based Community Development (ABCD) approach, which focuses on maximizing local potential such as active community participation, support from local government, and the availability of cleaning facilities and equipment. The implementation of the activity included preparation stages, manual cleaning along riverbanks, and the use of heavy equipment to remove large quantities of weeds and waste. The results indicate an improvement in river cleanliness and an increased level of community awareness regarding environmental conservation efforts. These findings are consistent with previous studies emphasizing the importance of community involvement in maintaining the sustainability of river ecosystems. Overall, this activity contributes to the formation of a healthier environmental culture, encourages sustained participation, strengthens stakeholder synergy, and is expected to become a routine community-based program with long-term impacts for communities living around river areas.